Benefits of sanogenetic concept for athletic performance rehabilitation purposes - Leontiev, O. V.; Rodichkin, P. V.; Fokin, A. M. (Theory and Practice of Physical Culture, 2020)
Sanogenetic approach to health issues has expanded our understanding of the health protection technologies. The sanogenetic approach implies the efforts to harmonize the natural physiological responses critical for the athletic performance; protect health and secure athletic longevity, with a special consideration given to the bodily intersystem links and their complex. The study analyzes the idea of a universal rehabilitative sanogenetic approach-driven training model application in sports. Sampled for the Experimental Group were the 27-32 year-old male athletes (n=37) qualified Class I to WCMS, with the 8-25-years-long records in track and field sports. All of them were diagnosed with autonomic dysfunctions (fatigue, vegetative lability, intellectual mnestic dysfunctions, palpitations and astheno-neurotic states under mental/emotional stresses). Sampled for the Reference Group were the 24-33 year-olds (n=22) free of vegetative dysfunctions.